Reactivity studies of 1-Benzoyl-3-(2,4,6-tri-tert-butylphenyl)thiourea and related ligands : a dissertation presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Chemistry at Massey University, Palmerston North, New Zealand - Chandrasena, Indira I.K.G. (Massey University, 2001)
This thesis aims to investigate the coordination modes, reactivity, spectroscopy and structures of bulky 1-benzoyl-3-(aryl)thioureas, with metals and non-metals. The bulky ligand, 1-benzoyl-3-(2,4,6-tri-tert-butylphenyl)thiourea (BzͭBPtuH) and the related ligands, 1-benzoyl-3-(2,4,6-triphenylphenyl)thiourea (BzPPtuH), 1-benzoyl-3-(2,6-diisopropylphenyl)thiourea (BzͥPPtuH), 1-benzoyl-3-(4-fluorophenyl)thiourea (BzFPtuH), and 1-benzoyl-3-phenylthiourea (BzPtuH) are the focus of the research in this thesis. Chapter One gives a brief review of the chemistry of thiourea and modified thiourea ligands. In Chapter Two, the preparation, characterization and structure of BzͭBPtuH are described and compounds of the type [M(L)₂] (M = Cu, L = BzͭBPtu or BzͥPPtu), [M(LH)₂X₂] (M = Cu(II) or Co(II), LH = BzͭBPtuH or BzͥPPtuH, X = Cl; M = Ni(II), LH = BzͭBPtuH, X = I), [M(LH)₂Cl] (M = Cu(I), LH = BzͭBPtuH, BzPPtuH, BzͥPPtuH or BzFPtuH), [Cu(BzPtuH)₃Cl] and [M(LH)⁴]PF⁶ (M = Cu(I) or Ag(I), LH = BzͭBPtuH or BzͥPPtuH) have been synthesized. The deprotonated ligands, BzͭBPtu and BzͥPPtu, in the complexes [Cu(BzͭBPtu)₂] and [Cu(BzͥPPtu)₂] coordinate through the O and S atoms resulting in six-membered chelate rings from the anionic ligands. The electronic spectra give support for thiocarbonyl S being bound to the metal. This, combined with ESR spectra suggests square planar structures for [M(L)₂] (L = BzͭBPtu or BzͥPPtu). For [Cu(BzͭBPtuH)₂Cl₂], the ligand remains neutral and binds through the S atom to form a distorted tetrahedral complex. The X-ray crystal structure of [Cu(BzͭBPtuH-K¹-S)₂Cl] shows the ligand is bound through S and the complex has a trigonal planar structure. The X-ray structure of [Co(BzͭBPtuH)₂Cl₂] shows it to be distorted tetrahedral with cobalt having an S₂C1₂ donor set. The complexes [M(LH)₄]PF₆ (M = Cu(I) or Ag(I), LH = BzͭBPtuH or BzͥPPtuH) probably have tetrahedral structures. In Chapter Three, HgCl₂ compounds of the type [Hg(LH)₂Cl₂] (LH = BzͭBPtuH, BzͥPPtuH or BzFPtuH) are reported as well as [Hg(BzPtuH)Cl₂]. With Hg(Ac)₂, the ligands (in alcoholic solvents) are converted to [C₆H₅CON=C(OX)NHR] (R = 2,4,6-tri-tert-butylphenyl, 2,4,6-tri-phenylphenyl, 2,6-diisopropylphenyl, p-fluorophenyl or phenyl, X = C₂H₅ and R = 2,4,6-tri-tert-butylphenyl, X = CH₃, or CH₂C₆H₅) while in CH₂Cl₂ [C₆H₅CON(COCH₃)C(O)NHR] (R = 2,6-diisopropylphenyl) or NHCN-(2,4,6-tri-tert-butyl)phenyl are obtained. With sodium ethoxide in alcohol and water NH₂-C(S)NH-(2,4,6-tri-tert-butyl)phenyl was isolated. For [Hg(LH)₂Cl₂] (LH = BzͭBPtuH, BzͥPPtuH or BzFPtuH) the ligand remains neutral and binds through the S atom to form a monomeric distorted tetrahedral complex. The structure of [Hg(BzͭBPtuH-K¹S)₂Cl₂] was determined crystallographically. The complex Hg(BzPtuH)Cl₂ is possibly a polymer containing Cl and S bridges. The intermediate mercury complex formed with Hg(Ac)₂ in alcohol reaction was unstable, and it decomposed to form HgS and a new compound [C₆H₅CON=C(OX)NHR]. The X-ray crystal structure and spectroscopic data confirm the final product. Cd(Ac)₂ reacted with BzͭBPtuH in ethanol to give some CdS, unreacted starting material and a little BzEͭBPA. No reaction was observed with Zn²⁺ or UO₂²⁺ acetate. Chapter Four investigates the coordination chemistry and reactivity of BzͭBPtuH and related ligands with halogens (I₂ and Br₂). The I₂ adducts of the type [(LH)I₂] (LH = BzͭBPtuH, BzPPtuH, BzͥPPtuH, BzFPtuH or BzPtuH) were obtained in 1:1 molar ratio as well as the metastable Br₂ adduct [(BzͥPPtuH)Br₂]. The X-ray crystal structure of [(BzͭBPtuH-K¹S)I₂] shows a I-I bond distance of 2.8537(4) Å. The X-ray crystal structure of [(BzͥPPtuH-k¹S)Br₂], shows a Br-Br bond distance of 2.6118(4) Å. The Br茢 adduct that initially formed in ice-cooled conditions with BzͭBPtuH was converted to a novel heterocyclic ring compound, 2-benzamido-5,7-di-tert-butylbenzothiazole hydrobromide (BͭBBTH) at room temperature. This compound is ionic with Br̶ anions and benzothiazole cations. In Chapter Five, the complexes [Rh(COD)(LH)Cl] (LH = BzͭBPtuH, BzPPtuH, BzͥPPtuH, BzFPtuH or BzPtuH; COD = 1,5-cyclooctadiene) are prepared from the reaction of [Rh(COD)Cl]₂ with the appropriate LH, and the complexes [Pt(LH)₂Cl₂] (LH = BzͭBPtuH or BzͥPPtuH) by reacting K₂[PtCl₄] with the appropriate LH. The X-ray structure of [Rh(COD)(BzPPtuH-K¹S)Cl] shows a square planar arrangement of the ligands about Rh, with LH binding through the sulfur atom. One of the π-bonds of COD is bound to Rh and is trans to the Cl group while the other π-bond is bound to Rh but is trans to the S atom. The two equivalent protons associated with the olefinic bonds trans to the Cl group have a different chemical shift from the two protons on the olefin arm trans to the S atom at low temperature (–20 to –40°C), but coalesce into one broad band at higher temperature (20 to 40°C). A preliminary X-ray structure on [Pt(BzͭBPtuH-K¹S)₂Cl₂] shows the complex has a cis structure.
Keywords: Thiourea; Ligands